The Efficacy and Safety of Esmolol for Septic Shock: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Huang, Po; Zheng, Xiangchun; Liu, Zhi; Fang, Xiaolei (Frontiers in Pharmacology, 2021)
Purpose: The meta-analysis aims to identify whether septic shock patients can benefit from esmolol. Materials and Methods: The relevant studies from MEDLINE, Cochrane Library, Embase were searched by two independent investigators using a variety of keywords. Stata software (version 12.0, Stata Corp LP, College Station, TX, USA)was used for statistical analysis. Results: A total of 14 studies were identified and incorporated into the meta-analysis. For overall analysis, the treatment of esmolol was associated with decreased 28-day mortality (RR=0.66, 95% CI=0.56-0.77, P＜0.001). Meanwhile, our analysis found that, esmolol could decrease HR (SMD: -1.70; 95% CI: [-2.24-(-1.17)], cTnI (SMD: -1.61; 95% CI: [-2.06-(-1.16)] compared with standard treatment. No significant differences between the two groups were found in MAP, Lac, CI and SVI. Conclusions: For septic shock patients with tachycardia, when the heart rates meet 100≤HR≤120, clinicians could choose esmolol to control heart rates. Further high-quality and large-scale RCT should be performed to verify it and screening more suitable patients.